4.2.1 Problems 1 to 100

Table 4.21: Problems not solved by Maple

#

ODE

Mathematica

Maple

39

\[ {}y^{\prime } = y^{2}+x^{2}-1 \]

232

\[ {}y y^{\prime \prime } = 6 x^{4} \]

416

\[ {}x^{2} y^{\prime }+y = 0 \]

417

\[ {}x^{3} y^{\prime } = 2 y \]

459

\[ {}x^{2} y^{\prime \prime }+\cos \left (x \right ) y^{\prime }+x y = 0 \]

460

\[ {}3 x^{3} y^{\prime \prime }+2 x^{2} y^{\prime }+\left (-x^{2}+1\right ) y = 0 \]

472

\[ {}x^{3} \left (1-x \right ) y^{\prime \prime }+\left (3 x +2\right ) y^{\prime }+x y = 0 \]

491

\[ {}x^{2} y^{\prime \prime }+\left (3 x -1\right ) y^{\prime }+y = 0 \]

492

\[ {}x^{3} y^{\prime \prime }-x y^{\prime }+y = 0 \]

608

\[ {}[x^{\prime }\left (t \right ) = t x \left (t \right )-y \left (t \right )+{\mathrm e}^{t} z \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )+t^{2} y \left (t \right )-z \left (t \right ), z^{\prime }\left (t \right ) = {\mathrm e}^{-t} x \left (t \right )+3 t y \left (t \right )+t^{3} z \left (t \right )] \]

783

\[ {}y^{\prime } = 1+x^{2}+y^{2}+x^{2} y^{4} \]

1058

\[ {}x^{2} y^{\prime }+y = 0 \]

1059

\[ {}x^{3} y^{\prime } = 2 y \]

1135

\[ {}y^{\prime } = \frac {-{\mathrm e}^{-x}+x}{{\mathrm e}^{y}+x} \]

1200

\[ {}{\mathrm e}^{x} \sin \left (y\right )+3 y-\left (3 x -{\mathrm e}^{x} \sin \left (y\right )\right ) y^{\prime } = 0 \]

1203

\[ {}x \ln \left (x \right )+x y+\left (\ln \left (x \right ) y+x y\right ) y^{\prime } = 0 \]

1360

\[ {}u^{\prime \prime }+u^{\prime }+\frac {u^{3}}{5} = \cos \left (t \right ) \]

1463

\[ {}t \left (t -1\right ) y^{\prime \prime \prime \prime }+{\mathrm e}^{t} y^{\prime \prime }+4 t^{2} y = 0 \]

1608

\[ {}y^{\prime } = \frac {x^{2}+y^{2}}{\sin \left (x \right )} \]

1609

\[ {}y^{\prime } = \frac {{\mathrm e}^{x}+y}{x^{2}+y^{2}} \]

1611

\[ {}y^{\prime } = \frac {x^{2}+y^{2}}{\ln \left (x y\right )} \]

1612

\[ {}y^{\prime } = \left (x^{2}+y^{2}\right ) y^{{1}/{3}} \]

1614

\[ {}y^{\prime } = \ln \left (1+x^{2}+y^{2}\right ) \]

1616

\[ {}y^{\prime } = \sqrt {x^{2}+y^{2}} \]

1618

\[ {}y^{\prime } = \left (x^{2}+y^{2}\right )^{2} \]

1689

\[ {}2 x^{2}+8 x y+y^{2}+\left (2 x^{2}+\frac {x y^{3}}{3}\right ) y^{\prime } = 0 \]

1691

\[ {}y \sin \left (x y\right )+x y^{2} \cos \left (x y\right )+\left (x \sin \left (x y\right )+x y^{2} \cos \left (x y\right )\right ) y^{\prime } = 0 \]

1696

\[ {}3 x^{2} \cos \left (x \right ) y-x^{3} y \sin \left (x \right )+4 x +\left (8 y-x^{4} \sin \left (x \right ) y\right ) y^{\prime } = 0 \]

2178

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+2 y^{\prime }-2 y = {\mathrm e}^{2 x} \left (\left (-x^{2}+5 x +27\right ) \cos \left (x \right )+\left (9 x^{2}+13 x +2\right ) \sin \left (x \right )\right ) \]

2347

\[ {}y^{\prime } = y^{2}+\cos \left (t^{2}\right ) \]

2350

\[ {}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2} \]

2351

\[ {}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2} \]

2352

\[ {}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2} \]

2353

\[ {}y^{\prime } = y+{\mathrm e}^{-y}+{\mathrm e}^{-t} \]

2354

\[ {}y^{\prime } = y^{3}+{\mathrm e}^{-5 t} \]

2356

\[ {}y^{\prime } = \left (4 y+{\mathrm e}^{-t^{2}}\right ) {\mathrm e}^{2 y} \]

2357

\[ {}y^{\prime } = {\mathrm e}^{-t}+\ln \left (1+y^{2}\right ) \]

2442

\[ {}t \left (t -2\right )^{2} y^{\prime \prime }+t y^{\prime }+y = 0 \]

2445

\[ {}\left (-t^{2}+1\right ) y^{\prime \prime }+\frac {y^{\prime }}{\sin \left (t +1\right )}+y = 0 \]

2453

\[ {}t^{3} y^{\prime \prime }-t y^{\prime }-\left (t^{2}+\frac {5}{4}\right ) y = 0 \]

2515

\[ {}2 t \cos \left (y\right )+3 t^{2} y+\left (2 y+2 t^{2}\right ) y^{\prime } = 0 \]

2525

\[ {}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2} \]

2526

\[ {}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2} \]

2527

\[ {}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2} \]

2528

\[ {}y^{\prime } = y+{\mathrm e}^{-y}+{\mathrm e}^{-t} \]

2529

\[ {}y^{\prime } = y^{3}+{\mathrm e}^{-5 t} \]

2531

\[ {}y^{\prime } = \left (4 y+{\mathrm e}^{-t^{2}}\right ) {\mathrm e}^{2 y} \]

2532

\[ {}y^{\prime } = {\mathrm e}^{-t}+\ln \left (1+y^{2}\right ) \]

2538

\[ {}y^{\prime } = y+{\mathrm e}^{-y}+2 t \]

2540

\[ {}y^{\prime } = \frac {t^{2}+y^{2}}{1+t +y^{2}} \]

2592

\[ {}y^{\prime \prime }+p \left (t \right ) y^{\prime }+q \left (t \right ) y = t +1 \]

2639

\[ {}t \left (t -2\right )^{2} y^{\prime \prime }+t y^{\prime }+y = 0 \]

2642

\[ {}\left (-t^{2}+1\right ) y^{\prime \prime }+\frac {y^{\prime }}{\sin \left (t +1\right )}+y = 0 \]

2659

\[ {}t^{2} y^{\prime \prime }+\left (-t^{2}+1\right ) y^{\prime }+4 t y = 0 \]

2789

\[ {}[x^{\prime }\left (t \right ) = x \left (t \right )-x \left (t \right )^{2}-2 x \left (t \right ) y \left (t \right ), y^{\prime }\left (t \right ) = 2 y \left (t \right )-2 y \left (t \right )^{2}-3 x \left (t \right ) y \left (t \right )] \]

2790

\[ {}[x^{\prime }\left (t \right ) = -b x \left (t \right ) y \left (t \right )+m, y^{\prime }\left (t \right ) = b x \left (t \right ) y \left (t \right )-g y \left (t \right )] \]

2795

\[ {}[x^{\prime }\left (t \right ) = -1-y \left (t \right )-{\mathrm e}^{x \left (t \right )}, y^{\prime }\left (t \right ) = x \left (t \right )^{2}+y \left (t \right ) \left ({\mathrm e}^{x \left (t \right )}-1\right ), z^{\prime }\left (t \right ) = x \left (t \right )+\sin \left (z \left (t \right )\right )] \]

2812

\[ {}\left [x_{1}^{\prime }\left (t \right ) = x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -\frac {\left (x_{1} \left (t \right )^{2}+\sqrt {x_{1} \left (t \right )^{2}+4 x_{2} \left (t \right )^{2}}\right ) x_{1} \left (t \right )}{2}\right ] \]

2814

\[ {}[x^{\prime }\left (t \right ) = x \left (t \right )-x \left (t \right )^{3}-x \left (t \right ) y \left (t \right ), y^{\prime }\left (t \right ) = 2 y \left (t \right )-y \left (t \right )^{5}-y \left (t \right ) x \left (t \right )^{4}] \]

2815

\[ {}[x^{\prime }\left (t \right ) = x \left (t \right )^{2}+y \left (t \right )^{2}+1, y^{\prime }\left (t \right ) = x \left (t \right )^{2}-y \left (t \right )^{2}] \]

2817

\[ {}[x^{\prime }\left (t \right ) = 6 x \left (t \right )-6 x \left (t \right )^{2}-2 x \left (t \right ) y \left (t \right ), y^{\prime }\left (t \right ) = 4 y \left (t \right )-4 y \left (t \right )^{2}-2 x \left (t \right ) y \left (t \right )] \]

2818

\[ {}[x^{\prime }\left (t \right ) = \tan \left (x \left (t \right )+y \left (t \right )\right ), y^{\prime }\left (t \right ) = x \left (t \right )+x \left (t \right )^{3}] \]

2906

\[ {}2 x +3 y+2+\left (y-x \right ) y^{\prime } = 0 \]

2909

\[ {}3 x -y+2+\left (x +2 y+1\right ) y^{\prime } = 0 \]

2924

\[ {}x y^{2}+2 y+\left (2 y^{3}-x^{2} y+2 x \right ) y^{\prime } = 0 \]

2955

\[ {}\left (x^{2}+y^{2}-2 y\right ) y^{\prime } = 2 x \]

2956

\[ {}y-x^{2} \sqrt {x^{2}-y^{2}}-x y^{\prime } = 0 \]

3034

\[ {}\sec \left (y\right )^{2} y^{\prime } = \tan \left (y\right )+2 x \,{\mathrm e}^{x} \]

3275

\[ {}y^{\prime \prime } = {y^{\prime }}^{2} \cos \left (x \right ) \]

3279

\[ {}\left (1+{y^{\prime }}^{2}\right )^{2} = y^{2} y^{\prime \prime } \]

3280

\[ {}y^{\prime \prime } = {y^{\prime }}^{2} \sin \left (x \right ) \]

3287

\[ {}1+\left (2 y-x^{2}\right ) {y^{\prime }}^{2}-2 y {y^{\prime }}^{2} x^{2} = 0 \]

3290

\[ {}y {y^{\prime }}^{2} x +\left (x y-1\right ) y^{\prime } = y \]

3371

\[ {}x^{3} \left (x^{2}+3\right ) y^{\prime \prime }+5 x y^{\prime }-\left (1+x \right ) y = 0 \]

3512

\[ {}y^{\prime \prime }+\frac {y}{z^{3}} = 0 \]

3678

\[ {}y^{\prime }+p \left (x \right ) y+q \left (x \right ) y^{2} = r \left (x \right ) \]

3684

\[ {}y \,{\mathrm e}^{x y}+\left (2 y-x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0 \]

3892

\[ {}\left [x_{1}^{\prime }\left (t \right ) = t \cot \left (t^{2}\right ) x_{1} \left (t \right )+\frac {t \cos \left (t^{2}\right ) x_{3} \left (t \right )}{2}, x_{2}^{\prime }\left (t \right ) = \frac {x_{2} \left (t \right )}{t}-x_{3} \left (t \right )+2-t \sin \left (t \right ), x_{3}^{\prime }\left (t \right ) = \csc \left (t^{2}\right ) x_{1} \left (t \right )+x_{2} \left (t \right )-x_{3} \left (t \right )+1-\cos \left (t \right ) t\right ] \]

4009

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x \left (x -3\right )}-\frac {y}{x^{3} \left (x +3\right )} = 0 \]

4079

\[ {}y^{2} \left (x^{2}+1\right )+y+\left (2 x y+1\right ) y^{\prime } = 0 \]

4251

\[ {}\sin \left (x \right ) \tan \left (y\right )+1+\cos \left (x \right ) \sec \left (y\right )^{2} y^{\prime } = 0 \]

4253

\[ {}2 y^{2}-4 x +5 = \left (4-2 y+4 x y\right ) y^{\prime } \]

4354

\[ {}x^{2}+y^{3}+y+\left (x^{3}+y^{2}-x \right ) y^{\prime } = 0 \]

4668

\[ {}y^{\prime } = f \left (x \right )+a y+b y^{2} \]

4670

\[ {}y^{\prime } = f \left (x \right )+g \left (x \right ) y+y^{2} a \]

4683

\[ {}y^{\prime } = f \left (x \right )+g \left (x \right ) y+h \left (x \right ) y^{2} \]

4696

\[ {}y^{\prime } = \operatorname {f0} \left (x \right )+\operatorname {f1} \left (x \right ) y+\operatorname {f2} \left (x \right ) y^{2}+\operatorname {f3} \left (x \right ) y^{3} \]

4699

\[ {}y^{\prime } = f \left (x \right )+g \left (x \right ) y+h \left (x \right ) y^{n} \]

4707

\[ {}y^{\prime }+\left (f \left (x \right )-y\right ) g \left (x \right ) \sqrt {\left (y-a \right ) \left (y-b \right )} = 0 \]

4712

\[ {}y^{\prime }+f \left (x \right )+g \left (x \right ) \sin \left (a y\right )+h \left (x \right ) \cos \left (a y\right ) = 0 \]

4726

\[ {}y^{\prime } = \left (1+\cos \left (x \right ) \sin \left (y\right )\right ) \tan \left (y\right ) \]

4728

\[ {}y^{\prime }+f \left (x \right )+g \left (x \right ) \tan \left (y\right ) = 0 \]

4739

\[ {}2 y^{\prime } = 2 \sin \left (y\right )^{2} \tan \left (y\right )-x \sin \left (2 y\right ) \]

4807

\[ {}x y^{\prime } = \sin \left (x -y\right ) \]

4986

\[ {}x^{k} y^{\prime } = a \,x^{m}+b y^{n} \]

5017

\[ {}y y^{\prime }+x^{3}+y = 0 \]

5020

\[ {}y y^{\prime }+f \left (x \right ) = g \left (x \right ) y \]

5072

\[ {}\left (\tan \left (x \right ) \sec \left (x \right )-2 y\right ) y^{\prime }+\sec \left (x \right ) \left (1+2 y \sin \left (x \right )\right ) = 0 \]

5120

\[ {}x \left (a +y\right ) y^{\prime }+b x +c y = 0 \]

5127

\[ {}\left (a +x \left (x +y\right )\right ) y^{\prime } = b \left (x +y\right ) y \]